Pengolahan Kerabang Telur Sebagai Pupuk untuk Kelompok Wanita Dusun 4 Desa Tincep Kecamatan Sonder - Rotinsulu, Merri Diana (Jujurnal Publisher, 2026)
The purpose of this activity is to provide an introduction and training on the use of eggshells as fertilizer. The problem in this activity is the limited knowledge of the use of organic fertilizer from eggshells. The target of this activity is the women's group in Hamlet 4, Tincep Village. The implementation of this activity includes counseling and training on processing eggshells as fertilizer. The variables observed were (1) participant enthusiasm and (2) participant attitudes towards the extension and training materials. The results of this activity are the level of enthusiasm of participants 10% moderate and 90% high, the attitude of participants towards the counseling and training materials 10% do not accept and 90% accept, there is an increase in knowledge and encourages increased skills in making organic liquid fertilizer from eggshells that can be used to loosen the soil and provide nutrients for flowers planted in polybags. The conclusion is that the women's group in Hamlet 4, Tincep Village, Sonder District is very enthusiastic and well accepts the processing of eggshells as fertilizer.